A rationally designed polysulfide-trapping interface on the polymeric separator for high-energy Li–S batteries. (December 2017) - Chang, Chi-Hao; Chung, Sheng-Heng; Nanda, Sanjay; Manthiram, Arumugam
Abstract: A coating layer consisting of a layer of graphene oxide (GO) inserted in between two layers of multi-walled carbon nanotubes (MWCNT) forms a multifunctional polysulfide-trapping triple-interface on the polymeric separator for lithium–sulfur (Li–S) batteries. The top and bottom highly conductive MWCNT interfaces are able to physically inhibit polysulfide diffusion and effectively reutilize the trapped active material during cycling. The inserted ultrathin GO layer with negatively charged carboxyl groups, on the other hand, electrostatically repels the migrating polysulfide anions. The stacked GO sheets also extensively prolong the migration routes of the polysulfides. Additionally, the "buffer zones" interspersed within the triple-interface accommodate the migrating polysulfides. Thus, the sandwiched separators enable Li–S cells with a high-sulfur-loading (10 mg cm −2 ), high areal capacity (10.9 mA h cm −2 ), and stable cycling ability even though the coating layer is ultra-thin (∼17 μm) and light-weight (∼0.23 mg cm −2 ). Graphical abstract: Sandwiched separators with a rational coating arrangement of MWCNT/GO/MWCNT serve as an effective polysulfide-trapping triple-interface. The "buffer zones" interspersed within the triple-interface offer well-secured spaces to further inhibit polysulfide diffusion. High-loading sulfur cathodes equipped with the sandwiched separators display stable electrochemical performances. Highlights: Sandwiched separators offer an effective polysulfide-trapping triple-interface. "Buffer zones" interspersed within the triple-interface inhibits polysulfide diffusion. Li–S cells with a high sulfur loading exhibit superior electrochemical performance.